The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcp.26271
|View full text |Cite
|
Sign up to set email alerts
|

Methylation‐associated DOK1 and DOK2 down‐regulation: Potential biomarkers for predicting adverse prognosis in acute myeloid leukemia

Abstract: DOK-1 and DOK-2 (DOK1/2) are closely related members of downstream of tyrosine kinase (DOK) family genes, which are found to be frequently rearranged in several hematopoietic cancers. However, the clinical implications of DOK1/2 in acute myeloid leukemia (AML) remain largely unknown. To investigate the clinical significance, real-time quantitative PCR (RQ-PCR) was carried out to detect DOK1/2 expressions in 125 de novo AML patients and 28 healthy controls. Real-time quantitative methylation-specific PCR (RQ-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…DOK family genes disorders have been reported in many cancers [9] , [18] , [19] , [20] . Although DOK family genes expression is closely associated related with pathological progression and poorer prognosis in some tumors, there has been no comprehensive analysis of DOK family genes in different cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOK family genes disorders have been reported in many cancers [9] , [18] , [19] , [20] . Although DOK family genes expression is closely associated related with pathological progression and poorer prognosis in some tumors, there has been no comprehensive analysis of DOK family genes in different cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that abnormal DOK gene expression is closely related to leukemia [9] , lung cancer [10] , gastric cancer [11] , colorectal cancer [11] , [12] , and breast cancer [13] , [14] . However, most of the studies are conducted in cell lines and/or animal models, and systematic studies have not been conducted in human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) and reverse transcribed into cDNA as described previously [26]. Real-time quantitative PCR (RT-qPCR) was performed using AceQ qPCR SYBR Green Master Mix (Vazyme Biotech Co., Piscataway, NJ, USA) on a 7500 Thermo cycler (Applied Biosystems, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR (RT-qPCR) was performed using AceQ qPCR SYBR Green Master Mix (Vazyme Biotech Co., Piscataway, NJ, USA) on a 7500 Thermo cycler (Applied Biosystems, CA). Reaction conditions and PCR cycling were conducted as previously described [26], adjusting only for optimized primer annealing temperatures (60 °C). PCR primers were designed using Primer Premier 6 (Premier Biosoft, Palo Alto, CA, USA), and the primer sequences were listed in Additional file 1: Table S2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation